2021
DOI: 10.24042/jipfalbiruni.v10i1.8341
|View full text |Cite
|
Sign up to set email alerts
|

Trending Research Topics in the Field of Physics Education from 2017 to 2019 in Highly Reputable International Journals

Abstract: This study aims to map the physics education research topics trending in the last three years in highly reputable international journals. This is a descriptive study that analyzed 511 articles using content analysis. All articles were selected from the top 3 academic journals: International Journal of Science Education (IJSE), Research in Science Education (RISE), and Science Education (SE). All three journals have JSRs above 0.8 with a quartile of Q1. Data collection and analysis were carried out from April t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We also utilize almost the whole section of the body of the research paper. Thus, our current study can suggest that LDA considers the more comprehensive nature of thematic analysis rather than using the keywords from research titles as reported by Faisal [14] or selecting small parts of documents [13,[15][16][17]. Second, the distributional hypothesis of topics and the mixed membership of topics have been satisfied through the LDA algorithm.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We also utilize almost the whole section of the body of the research paper. Thus, our current study can suggest that LDA considers the more comprehensive nature of thematic analysis rather than using the keywords from research titles as reported by Faisal [14] or selecting small parts of documents [13,[15][16][17]. Second, the distributional hypothesis of topics and the mixed membership of topics have been satisfied through the LDA algorithm.…”
Section: Discussionmentioning
confidence: 95%
“…These advantages have explained the existence of multidisciplinary aspects of physics education research. Categorization of a single topic in each document as reported by Faisal, et al [14] and Bancong, et al [13] fails to represent that each topic should be interchangeably in each document. Nevertheless, in nature, our paper is dedicated to the aim of exploration and attempts to deliver a promising tool to conduct a more efficient methodology of thematic analysis which successfully helps us to add dimensions of analysis and visualization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the revised 2013 curriculum, the term scientific approach is also known. In learning with a scientific method, students become more active (Bancong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%